Reprezentacja logiczna temporalnych aspektów prawa - Mach, Maria; Gaweł, Tomasz (Logical representation of temporal aspects in law, 2005)
The paper concerns the problem of logical formalisation of temporal aspects in law. It contains a detailed presentation of all types of temporal relations that can be met in legal texts, as well as the discussion on temporal legal aspects. Two examples of temporal legal knowledge and its representation are presented: one taken from the literature, one elaborated by the authors. These examples clearly prove the need for using a temporal representation as a formal tool for describing and analysing enterprises’ environment, that changes in time.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1064, s. 146-158